Perancangan Taman Gizi Terpadu Pedukuhan Gumulan di Kelurahan Caturharjo - Binarti, Floriberta; Kristiawan, Yanuarius Benny; Darmono, Evelyn Christabel; Maria Erika Febryanti (Jurnal Atma Inovasia, 2022)
Gumulan village, one of 14 villages in Caturharjo Village, has the highest population density, which launched a movement of 14 vegetable villages in the form of a nutrition garden. This community service activity aimed to assist the Gumulan Village in reviving a nutrition garden that was abandoned due to the pandemic through an integrated nutrition garden design service with a green architecture approach. The added facilities based on the results of the identification of the village’s problems and potency are intended to optimize the land use, empower communities and natural resources (bamboo), and develop local arts, which lead to improving the health and welfare of the population without destroying the environment. With the concept of green architecture, an integrated nutrition garden design can be realized as a space for gardening, exercising, playing, culinary tours, and performances that suit the environmental context.